The effect of task (mis)matching and self-selection on intrinsic motivation and performance - Freyer, Timo; Radbruch, Jonas; Schaube, Sebastian; Strang, Louis (Journal of economic behavior & organization, 2025)
This paper investigates how the self-selection of tasks affects worker performance. Specifically, it investigates the impact of aligning tasks with workers’ preferences and the effect of providing workers with greater autonomy in choosing their tasks. To answer these questions, we conducted an online experiment in which participants engaged in one of two real-effort tasks. We exogenously varied whether participants were either randomly assigned their preferred or non-preferred task, or if they had the opportunity to actively self-select their task. The results show that participants who were randomly assigned their preferred task or self-selected a task increased their output by about 25%–42% of a standard deviation compared to those who were assigned their non-preferred task. This increase in output is linked to both enhanced productivity and extended time spent working on the task. In essence, our results underscore that workers’ performance depends crucially on whether they work on their preferred task. Importantly, our results also document that granting workers decision autonomy in task selection reinforces the performance increase. •Real-effort experiment on how task-allocation procedures affect performance.•Tasks are either randomly assigned, or self-selected.•Performance increases if subjects work on preferred vs. non-preferred task.•Performance increases if subjects self-select vs. get assigned preferred task.